2004
DOI: 10.1073/pnas.0402200101
|View full text |Cite
|
Sign up to set email alerts
|

Switching desaturase enzyme specificity by alternate subcellular targeting

Abstract: The functionality, substrate specificity, and regiospecificity of enzymes typically evolve by the accumulation of mutations in the catalytic portion of the enzyme until new properties arise. However, emerging evidence suggests enzyme functionality can also be influenced by metabolic context. When the plastidial Arabidopsis 16:0⌬ 7 desaturase FAD5 (ADS3) was retargeted to the cytoplasm, regiospecificity shifted 70-fold, ⌬ 7 to ⌬ 9 . Conversely, retargeting of two related cytoplasmic 16:0⌬ 9 Arabidopsis desatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 43 publications
4
79
0
2
Order By: Relevance
“…Metabolic context has been shown to affect enzyme regiospecificity when subcellular location was altered as in the case of a fatty acid desaturase (Heilmann et al, 2004). The distribution of isoprenoid synthase products in a given organism is also influenced by nonenzymatic factors such as salt and metal ion concentrations, or the available concentration of substrates, conditions that have been studied in vitro (Fujii, 1980;Matsuoka et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic context has been shown to affect enzyme regiospecificity when subcellular location was altered as in the case of a fatty acid desaturase (Heilmann et al, 2004). The distribution of isoprenoid synthase products in a given organism is also influenced by nonenzymatic factors such as salt and metal ion concentrations, or the available concentration of substrates, conditions that have been studied in vitro (Fujii, 1980;Matsuoka et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has previously been shown that desaturases can have additional functionality, such as acting as conjugases (25) or hydroxylases (26), different positional specificities depending on the type of lipid to which the substrate is conjugated (27), the chain length of the acyl group (28), or the ability of a soluble desaturase enzyme to catalyze two double bonds (⌬4 and ⌬9) into a saturated fatty acyl-ACP substrate (29), the ability of a desaturase enzyme to catalyze two double bonds (⌬12 and 3) on the same acyl chain (C18) has not previously been reported. It will be interesting to study how these ⌬12͞ 3 enzymes exert their dual positional specificity, because the regioselectivity of ⌬12 and 3 desaturases is Јv ϩ 3Ј (i.e., three carbons away from an existing double bond) and Ϫ3 (i.e., three carbons from the methyl end), respectively (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a prime determinant of regioselectivity 27 Å from the diiron site, at which double-bond formation occurs, is perhaps surprising, however, that regioselectivity can be affected by interaction of the acyl carrier moiety and desaturase is not without precedent. Within the evolutionarily distinct class of integral membrane enzymes, the FAD5 desaturase was shown to perform Δ7 desaturation when presented with 16∶0 esterified to monogalactosyldiacylglycerol, but Δ9 desaturation when presented with 16∶0 esterified to phosphatidyl choline (16). Thus, for both soluble and integral membrane desaturase, regioselectivity is controlled remotely, albeit by different mechanisms.…”
Section: Position 280 Of the Castor Desaturase Has A Strong Influence Onmentioning
confidence: 99%